Los lenguajes audiovisuales de YouTube : nuevos géneros y formatos en las producciones audiovisuales de youtubers argentinos - Ibañez, María Florencia (2022)
This work deals with the possible new genres and formats that reside in variants of audiovisual languages from amateur videos, hosted on the YouTube platform. Circumscribed to a hybridization of discursive genres mediated by the characteristics of Personal Media, the differences around Mass Media (Vacas, 2010) begin to emerge as users become content generators. This dynamic is due to the logic in which Personal Media centre the power on the user, who swarms the web permanently from different receiving devices, such as computers, cell phones and video game consoles; different from the spectator's relationship with the traditional media with which he lives in moments of leisure. \nTherefore, the Internet fosters a construction space of diffuse (or amateur) design, which coexists with expert design (in the hands of professionals) (Manzini, 2015). In a world where connectivity and convergence prevail, this type of design, which does not require academic knowledge of the technique, gives rise to a phenomenon on YouTube: the Youtubers. The content that these users generate is presented as dissimilar around the use of the most traditional Mass Media conventions. It can be inferred that the audiovisual productions of Argentine Youtubers, in particular, are grouped into genres and formats with an amateur aesthetic, and formats that respond to the logic of the web, inserted in a context that distinguishes them from their predecessors.